Knockdown of eIF3D inhibits breast cancer cell proliferation and invasion through suppressing the Wnt/β-catenin signaling pathway - Fan, Yan (Int J Clin Exp Pathol, 2015)
eIF3D (eukaryotic translation initiation factor 3 subunit D) is one member of the eIF3 family and plays a critical role in translation initiation. Previous studies showed that it was involved in the development and progression of several tumors. However, the role of eIF3D in breast cancer and the underlying mechanism is still unclear. Therefore, this study set out to investigate the role of eIF3D in breast cancer. Our results demonstrated that eIF3D is up-regulated in breast cancer cells. Knockdown of eIF3D inhibited breast cancer cell proliferation and invasion. In addition, knockdown of eIF3D inhibited the expression of β-catenin, cyclin D1 and c-Myc in breast cancer cells. Taken together, our findings show that siRNA-eIF3D inhibits breast cancer cell proliferation and invasion through suppressing the Wnt/β-catenin signaling pathway. Therefore, eIF3D may be a good molecular target for the prevention and treatment of breast cancer.